Selection of rice cultivars resistant to some pathogens using seed health testing - Soave, J.; Pizzinatto, M. A.; Usberti Junior, J. A.; Camargo, O. B.A.; Villela, O. V. (Pesquisa Agropecuaria Brasileira, 2014)
Thirty-six lowland rice (Oryza sativa L.) progenies have been tested in yield trials aiming at determining the most important seed-borne fungi and the progeny performance as to each of the pathogens found in seeds, with special emphasis on seed discoloration and consequent seed weight loss. Significant progeny differences as to seven seed-born fungi have been found; however, as far as seed discoloration and consequent seed weight loss are concerned, Rhynchosporium oryzae, Phoma spp., Trichoconis padwickii and Helminthosporium oryzae have been the most important pathogens. Seven progenies outperformed IAC-899 (commercial variety used as control) regarding all the parameters analysed. It is concluded that seed health testing is an effective complementary 1001 in selecting rice germplasms with lower seed-borne fungal incidence.